THE EFFECT OF MARKETING INNOVATION IN BUILDING THE MENTAL IMAGE OF THE ORGANIZATION THROUGH THE MEDIATING ROLE OF PRODUCT QUALITY-AN ANALYTICAL STUDY OF THE OPINIONS OF A SAMPLE OF WORKERS IN GOVERNMENT AND PRIVATE HOSPITALS IN THE HOLY CITY OF KARBALA (World Economics and Finance Bulletin, 2024)
The current study aim to test the correlation and influence relationships between the three variables (Marketing Innovation, the Mental Image of the Organization, Product Quality), and four hypotheses were designed to achieve this goal. All hypotheses were in the state of acceptance, thus confirming the existence of correlation and effect relationships. The research used the questionnaire as a tool to collect data from the target sample, which numbered (35 ) people, who work at government and private hospitals in the holy city of Karbala . the study used the statistical program spss to analyze the answers of the sample and reach the results that support the acceptance of the hypotheses. The research reached a set of conclusions that can serve decision makers in the health institutions investigated , the necessity of applying marketing innovation dimensions as a means to achieve the mental image of the organization through the product quality
Keywords: Marketing Innovation; the Mental Image of the Organization; Product Quality